2010
DOI: 10.1103/physrevb.81.214420
|View full text |Cite
|
Sign up to set email alerts
|

Muon spin relaxation in some multiferroic fluorides

Abstract: In all investigated systems SR revealed a linear F-+ -F "hydrogenlike" bonded complex with the F-F distance of 2.43͑2͒ Å in the paramagnetic phase. Two consecutive magnetic transitions were found in all systems, in agreement with the magnetic susceptibility measurements. Whereas in the paramagnetic phase the local magnetic fields at muon sites are about 20 G, they strongly increase below the Néel temperature T N and reach values of several kilogauss. The SR results further suggest that the system is inhomogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This family has received the most attention in the past three years. Initially discovered to be multiferroic below 122 K by Ravez et al (1989Ravez et al ( , 1990aRavez et al ( , 1990b, Ravez (1997) and Ishihara et al (1993Ishihara et al ( , 1994, it has been analyzed via dielectric studies (Blinc et al 2008), polaron studies (Levstik et al 2008(Levstik et al , 2009, magnetic resonance (Blinc et al 2009a) and muon spectroscopy (Potocnik et al 2010). In addition to its Néel temperature at 122 K, it has a structural transition at 290 K (Ishihara et al 1993(Ishihara et al , 1994.…”
Section: 23mentioning
confidence: 99%
“…This family has received the most attention in the past three years. Initially discovered to be multiferroic below 122 K by Ravez et al (1989Ravez et al ( , 1990aRavez et al ( , 1990b, Ravez (1997) and Ishihara et al (1993Ishihara et al ( , 1994, it has been analyzed via dielectric studies (Blinc et al 2008), polaron studies (Levstik et al 2008(Levstik et al , 2009, magnetic resonance (Blinc et al 2009a) and muon spectroscopy (Potocnik et al 2010). In addition to its Néel temperature at 122 K, it has a structural transition at 290 K (Ishihara et al 1993(Ishihara et al , 1994.…”
Section: 23mentioning
confidence: 99%
“…In addition, muon spin relaxation measurements in K 3 Cr 2 Fe 3 F 15 suggest that the system is inhomogeneous below 35 K, with magnetically ordered clusters being embedded in a disordered matrix. 10 One of the most spectacular manifestations of slow magnetic relaxation and non-ergodicity in a system is the magnetic memory effect. It has recently been shown that the magnetic memory effect can be utilized for digital information storage in a thermal memory cell.…”
mentioning
confidence: 99%